Zakhrebetnyye Tatars in Tyumen District of 17th -- First Third of 18th Century - G. K. Samigulov (Научный диалог, 2017)
One of the unsolved problems of history of the Turkic population of Western Siberia is considered about the group of Zakhrebetnye Tatars. It is noted that almost all researchers used in relation to the population the word zakhrebetnik , which for this period refers to dependent people, who did not have their own farms and worked and subsisted by other people’s yards. The novelty of the research is seen in the introduction into scientific circulation the new materials relating to various caste groups of Tatars of the Tyumen district. These materials allow to make different interpretation of the nature of Zakhrebetnye Tatars. It is proved that in the Tyumen district most of Zakhrebetnye Tatars were close relatives of serving Tatars (their brothers, sons, nephews) and were a personnel reserve for substitution of serving relatives who retired from service of old age or in death. It is reported that Zakhrebetnye Tatars owned - individually - arable and hay lands, and - in conjunction with Yasak Tatars - were the collective owners of patrimonial lands: hunting, fishing, hop, etc. It is emphasized that in this case Zakhrebetnye Tatars were exempt from paying tribute until 1730-ies and were in fact privileged group of the population.